Working fluid charge oriented off-design modeling of a small scale Organic Rankine Cycle system. (15th September 2017) - Liu, Liuchen; Zhu, Tong; Ma, Jiacheng
Highlights: Organic Rankine Cycle model considering working fluid charge has been established. Overall solution algorithm of system off-design performance is proposed. Variation trend of different zones in both heat exchangers can be observed. Optimal working fluid charge volume for different output work has been estimated. Abstract: Organic Rankine Cycle system is one of the most widely used technique for low-grade waste heat recovery. Developing of dynamic Organic Rankine Cycle models played an increasingly important part in system performance prediction. The present paper developed a working fluid charge oriented model for an small scale Organic Rankine Cycle to calculate the theoretical value of working fluid charge level for the system under rated condition. The two heat exchangers are divided into three different zones and related heat transfer correlations are employed to estimate the length variation of each zones. Steady state models have been applied to describe the performance of pump and expander. Afterwards, an overall solution algorithm based on the established model has been proposed in order to exact simulate the system's off-design performance. Additionally, the impact of different working fluid charge volumes has also been discussed. Simulation results clearly shows the variation trend of different zones in both heat exchangers, as well as the variation trend of system operating parameters under various expander output work. Furthermore, the highest thermal efficiency can be reached 6.37% under rated conditions with a working fluid charge volume of 34.6 kg.